The implementation of an advanced practice radiation therapy (APRT) program in Singapore. (March 2021) - Wong, Sharon M.M.; Sin, S.Y.; Lim, L.H.; Nurul Tassha, B.M.A.; Lin, Jeannie; Melissa, K.; Koh, W.Y.; Ho, Francis; Quah, Daniel S.C.; Sommat, Kiatissa; Tuan, Jeffrey K.L.; Wong, F.Y.; et al.
Abstract: Background: The exploration of Advanced Practiced Radiation Therapists (APRTs) development in Singapore started in 2011. This study aims to provide an overview of the development of the APRT roles, and to discuss the approaches used to develop and implement these roles in Singapore. Materials and methods: A mixed methods approach was used in the development of the APRT program. A literature review was carried out to define the APRT scope of practice and core responsibilities. A competency and assessment framework were setup to assess the core competency areas. With this framework, a structured 1-year residency training program was developed. Results: The scope of practice and core responsibilities of APRTs were defined with five proposed advanced practice profiles being successfully validated. A competency framework was set up to assess the core competency domains: clinical, technical and professional competencies, research, education and leadership. A 4-point scoring system was developed for the competency assessment based on two criteria; the frequency with which RTTs would demonstrate competency, and the ability of performing the task competently. A 1-year structured APRT residency program was developed and implemented. The programme consisted of structured lectures, and clinical practice-based modules where APRT residents receive structured mentoring under a mentorship program. Conclusion: The APRT program in Singapore employed an evidence-based implementation process that tested the feasibility of a new practice model. Multidisciplinary involvements, mentorship and clinical training were important factors for the success of the APRT program.